The Politics of Multifaith: The Limits of Legible Religion in Europe - Bobrowicz, Ryszard ca. 20./21. Jh. (Political and Public Theologies, 2025)
In this book, Ryszard Bobrowicz discusses why seemingly neutral rooms, multi-faith spaces, were subject to contestations from, and clashes between, their users, their managers, and those shaping policies concerning them. From street protests to parliamentary debates, from Sweden to Spain, this book explores the impact of multi-faith spaces in Europe by critically examining the visions of religion behind, in, and around them. Ryszard Bobrowicz investigates the history and intellectual foundations of the politics of multi-faith in contemporary Europe, introducing the novel notion of ‘legible religion’. According to Bobrowicz, in administrative proceedings, phenomena labelled as religious are reduced to the features that are deemed important by public functionaries. This has striking implications for both practice and politics.